STANDARISASI KOMPETENSI AKADEMIK CALON GURU SEKOLAH DASAR DALAM MATA PELAJARAN MATEMATIKA - Maratun Nafiah (Perspektif Ilmu Pendidikan, 2007)
The main objective of this research is to know the academic competence of primary school teacher candidates in mathematics for primary school. The competence is one of the requirements for primary school teacher candidates. This research employs descriptive method with quantitative approach and was conducted as from May through November 2005 in the Study Program of Elementary School Teacher Education, School of Education, State University of Jakarta. The result of the research shows that the competence of the primary school teacher candidates is far below the expectation in the subject mastery, teaching methodology, and evaluation system.